The Effect of Al-Qur'an Recitation as Systematic Audio Therapy on Patients with Neurodegenerative Progressive Supranuclear Palsy (PSP): A Review - Suryo, Nurrohim; Syafi'i, Muhammad Hisyam (Journal of Islamic Communication and Counseling, 2024)
Al-Quran, as the holy book in the Islamic religion, is not only a spiritual guide but also has a significant psychological impact on the individuals who read it. The Koran offers ethical and moral guidance and covers profound psychological aspects. Its influence is not only limited to religious aspects but also deepens humans' understanding of themselves and their environment. Neurodegenerative disorder refers to a process or condition where nerve cells in the central nervous system (i.e., brain and spinal cord) experience progressive damage or death. The damage leads to decreased cognitive function, behavioral changes, and motor disorders. The present study aims to provide an overview of the effect of listening to Al-Quran recitation as an intervention on neurodegenerative progressive supranuclear palsy (PSP) subjects. The current research used a literature review approach by collecting credible sources in books, scientific articles, documents, and previous research. The findings of this study illustrate that systematic Al-Quran intervention resulted in positive psychological and physiological benefits, especially on the brain's nerves. Thus, frequent, and further medical assistance is imperative for patients with PSP.